The ontology of complexity and the neo-Schumpeterian evolutionary theory of economic change - Robert, Veronica (2017)
Different studies have tried to find a common thread that places different evolutionary and neo-Schumpeterian contributions to economic change under one umbrella. The complexity approach can account for a set of attributes that evolutionary economics has been considering, as decentralized interaction, heterogeneous agents, bounded rationality, networks of linkages, non-linear dynamics, divergent paths, disequilibrium and emergent properties. In this regard, the complexity approach could be a theoretical and conceptual starting point that allows the integration of different contributions (Davis, 2008; Fontana, 2013). In this article, we attempt to show that complexity can also be useful to point out the profound differences between evolutionary strands. This paper analyzes how the ontological evolutionary assumptions of complexity are emphasized with different intensity by different groups of representative contributions of evolutionary economics. We propose that these differences reflect deeper issues related to two major concerns of economic theory: coordination and order vs. transformation and change of economic systems (Dosi and Orsenigo 1988). In this context, the hypothesis of the article is that complexity acts as an umbrella and at the same time as a differentiating criterion of different strands within evolutionary economics, since their ontological assumptions relate differentially to these two concerns. Using a bibliometric methodology, we identify a set of representative contributions for five strands of evolutionary economics. Additionally, we analyze how the various dimensions and attributes of complexity ontology are emphasized unevenly by each group of contributions. To show the differences, we quote fragments from contributions corresponding to the dimensions and attributes of the complexity and use a set of nonparametric tests to corroborate the significance of the differences in the frequency in which these references appear. The results show that, while groups concerned with coordination are focused on heterogeneity and networks assumptions, groups concerned with transformation stress path dependence and divergent dynamics. Emergent properties are common to all of them.